Exploring the level of preparedness to fire risk in schools in South Africa: A case study of four schools in Kayamandi Township, Stellenbosch - Mugamu, Eunison (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.